Examining The Influence of School Effectiveness, Knowledge Management, and School Based Budgeting on Teachers’ Work Motivation - Danisma, Danisma; Hendra, Robi; Habibi, Akhmad (Jurnal Paedagogy, 2026)
This study aims to examine the influence of school effectiveness, knowledge management, and school-based budgeting on teachers’ work motivation in educational settings. The research employed a quantitative approach with a non-experimental survey design (ex post facto). The sample consisted of 207 teachers from various schools in Jambi Province. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine the relationships among the study variables. The results indicate that the proposed model meets the criteria for good validity and reliability. Furthermore, all three independent variables have positive and statistically significant effects on teachers’ work motivation. Specifically, knowledge management contributes to increased motivation through processes of knowledge sharing and professional competence development. School effectiveness and school-based budgeting enhance teacher motivation by strengthening managerial systems, increasing teacher participation, and promoting transparency in school resource management. These findings confirm that improving school effectiveness, optimizing knowledge management practices, and implementing school-based budgeting are key determinants in fostering sustainable teacher work motivation and enhancing overall educational quality.